Hematologic and biochemical characteristics in patients with and without type 2 diabetes mellitus undergoing hemodialysis during a one-year follow-up period - Alvarez-Angeles, M. (2018)
Objective: To report if there are hematologic and biochemical differences among patients with and without type 2 diabetes mellitus (T2DM) undergoing hemodialysis (HD). Materials and methods: An observational, retrospective, cohort study of patients treated in the Renal Health Program at the Centro de Prevención de Enfermedad Renal S.A.C. (CENPER) in Lima, Peru. The hematologic and biochemical parameters of 3 patients with T2DM and 3 patients without T2DM undergoing HD were compared. Results: Significant differences (p < 0.05) were found in the lymphocyte percentage, lymphocyte/monocyte ratio (LMR), hemoglobin and hematocrit concentration (lower in diabetic patients), monocyte percentage, and neutrophil/ lymphocyte ratio (NLR) (higher in diabetic patients). In the biochemical parameters, the only significant difference was found in the glutamic-oxaloacetic transaminase (GOT) value, which was higher in the diabetic patients compared with the non-diabetic patients (p < 0.005). Conclusions: Diabetes is an important factor linked to inflammation, anemia, lymphopenia and monocytosis in patients undergoing HD. The LMR was the most powerful marker of inflammation in this patient series. Larger-scale studies are required to verify this evidence.